Analysis of Increasing Human Development Index (HDI) based Forecasting Approches - Hamsani Hamsani; M. Afdal Samsuddin; Achmad Affandi; Ricca Affressia (Universitas Bangka Belitung, 2023)
Abstract: The purpose of this study is to analyze strategies for increasing human development index (HDI) in South Bangka Regency, Bangka Belitung Islands Province, Indonesia, from 2010 to 2021 using descriptive analysis and forecasting methods using the exponential method. Human development index is measured by three components are education, health, and a decent standard of living. The results of this study show that increasing the human development index in Bangka Selatan Regency in the short term can be increased by increasing the standard of living component by increasing per capita spending, while the education and health components can be increased in the long term. the results of the forecasting show that from 2023 to 2031, the HDI in South Bangka Regency will continue to increase.